2015
DOI: 10.1007/s10597-015-9900-6
|View full text |Cite
|
Sign up to set email alerts
|

How People with Depression Receive and Perceive Mental Illness Information: Findings from the Australian National Survey of Mental Health and Wellbeing

Abstract: Despite the recognised importance of accurate mental illness information in help-seeking and improving recovery, little is known about the dissemination of such information to people with depression. With a view to informing effective communication to those most in need, we explored the extent to which mental illness information is received by people with depression, its perceived helpfulness and we characterise those who do not receive such information. Using data from the Australian National Survey of Mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Current information sources of people with depression are summarised in Table S 5 . Media was the most frequently reported source of information (32 studies), including browsing the internet (e.g., depression websites, search engines, Wikipedia; 27 studies, 84.4%) [ 6 , 15 , 16 , 18 , 20 22 , 30 32 , 39 , 41 , 42 , 44 47 , 51 , 52 , 56 , 57 , 60 , 61 , 63 , 64 , 68 , 69 ], broadcast media (11 studies, 34.4%) [ 31 , 38 , 39 , 44 , 47 , 51 53 , 68 70 ], and online forums/groups and social media (8 studies, 25.0%) [ 13 , 15 , 18 , 20 , 30 , 37 , 56 , 57 ]. Health professionals was also a frequently mentioned information source (31 studies), including general healthcare professionals (26 studies, 83.9%) [ 6 , 18 , 20 22 , 31 , 33 , 36 , 38 , 39 , 41 44 , 48 , 50 53 , 57 , 60 , 61 , 70 73 ], mental health professionals (12 studies, 38.7%) [ 6 , 18 <...…”
Section: Resultsmentioning
confidence: 99%
“…Current information sources of people with depression are summarised in Table S 5 . Media was the most frequently reported source of information (32 studies), including browsing the internet (e.g., depression websites, search engines, Wikipedia; 27 studies, 84.4%) [ 6 , 15 , 16 , 18 , 20 22 , 30 32 , 39 , 41 , 42 , 44 47 , 51 , 52 , 56 , 57 , 60 , 61 , 63 , 64 , 68 , 69 ], broadcast media (11 studies, 34.4%) [ 31 , 38 , 39 , 44 , 47 , 51 53 , 68 70 ], and online forums/groups and social media (8 studies, 25.0%) [ 13 , 15 , 18 , 20 , 30 , 37 , 56 , 57 ]. Health professionals was also a frequently mentioned information source (31 studies), including general healthcare professionals (26 studies, 83.9%) [ 6 , 18 , 20 22 , 31 , 33 , 36 , 38 , 39 , 41 44 , 48 , 50 53 , 57 , 60 , 61 , 70 73 ], mental health professionals (12 studies, 38.7%) [ 6 , 18 <...…”
Section: Resultsmentioning
confidence: 99%
“…A recent study done in PHC center visitor reports that overall 19% of men and women were found to have symptoms of depression in the past 2 weeks (Al-Qadhi, Rahman, Ferwana, & Abdulmajeed, 2014). Furthermore, a national-level study from Australia reports that those suffered from depression 54.7% received information (in descending order) from pamphlets, Internet, television, magazines, newspaper, radio and books; it further showed that those with low levels of education did not receive any information (Graham, Hasking, Clarke, & Meadows, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, a related body of work exists for seeking medical and mental health information on the Internet. There has been an increasing reliance on and use of the Internet for health and mental health information (Basch et al, 2018;Graham et al, 2015;Rainie & Fox, 2000;Reavley et al, 2011;Soreni et al, 2019). In addition, those that accessed information from the Internet have a higher likelihood of going to a mental health professional or a general medical practitioner for psychological issues (Reavley et al, 2011), further highlighting the importance of this study's focus on examining search strings used on search engines when looking for mental health services.…”
Section: Search String Generation and Utilizationmentioning
confidence: 95%